Processing induced segregation in PLA/TPS blends: Factors and consequences - M. Jozo; L. Cui; K. Bocz; B. Pukanszky (eXPRESS Polymer Letters, 2020)
Poly(lactic acid) (PLA) and thermoplastic starch (TPS) blends with two different glycerol contents were prepared by injection molding. Mechanical properties were characterized by tensile and impact testing, structure by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) as well as Raman spectroscopy, and water absorption was determined as a function of time. Compression-molded specimens were used as reference. The properties of the blends cover a wide range, stiffness changes from 3.3 to around 1.0 GPa, while strength from 54 to 22 MPa as TPS content increases from 0 to50 wt%. Heterogeneous structure forms in the blends because of the weak interaction of the components. Processing conditions do not change bulk properties. Weak interactions and the large difference in the viscosity of the components lead to the formation of a skin on the surface of the specimens. The skin consists mainly of PLA, while the core contains a larger amount of TPS. The thickness of the skin depends on processing technology and conditions; it is about 18 μm for the injectionmolded, while 4.5 μm for the compression-molded parts at 50 wt% TPS content. The development of the skin layer can be advantageous in some applications because it slows down water absorption considerably.